Dynamical Mechanical Properties of Polypropylene Composites Filled with Olive Pit Particles - (:unkn) unknown (AMER SOC TESTING MATERIALS, 2019)
Wood Polymer Composites (WPCs) have attracted attention in recent years because of growing ecological, social, and economic awareness. This study focuses on polymer composites filled with olive pit particles. In the present study, the test specimens were prepared with different ratios of mixtures that contain polypropylene (PP), olive pit particles in four different concentrations (5.0, 10.0, 15.0, and 20.0 wt%), and maleic anhydride as modifier. The mechanical, thermal, and viscoelastic properties of the WPC were obtained using Dynamic Mechanic Analyzer test equipment and a thermogravimetric differential thermal analyzer. Fourier transform infrared spectroscopy was carried out in order to determine the chemical bonds of these materials. The specimens were also characterized by scanning electron microscopy. The results of the study demonstrated that olive pit particles could be used as reinforcement for PP because of their good thermal and mechanical effects.
Keywords: olive pit particles; polypropylene; dynamic mechanic analyzer; thermogravimetric differential thermal analyzer; Fourier transform infrared spectroscopy